PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI TERHADAP KINERJA GURU PADA SMK YOS ANUGRAH BATAM - Amit Silitonga; Indra Firdiyansyah (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
This study aims to see the effect of principal leadership and motivation on teacher performance at SMK Yos Anugerah Batam. This research uses the census method, which is to record the total population. Based on the field census, the sample in this study was 33 employees. Data were collected using a questionnaire technique. In the research results the regression equation Y = 8,600 + 0,712X1 + 0,406X2 + 0,236X3 + e. The leadership variable has a significant direct influence on employee performance with a coefficient value of 0.419, the Work Motivation variable has a significant direct influence on employee performance with a coefficient value of 0.422, and the variables of leadership, work motivation and work discipline have a simultaneous effect on employee performance. R2 value is 76.8%. while the remaining 23.2% is explained by other variables not included in this study